Гострі ускладнення цукрового діабету у дітей, які отримують помпову інсулінотерапію - Глоба, Є. В.; Зелінська, Н. Б.; Ніфонтова, Л. В.; Погадаєва, Н. Л.; Бегутова, Т. М.; Хорошая, О. А. (Clinical Endocrinology and Endocrine Surgery, 2012)
We investigated the influence of different types of insulinotherapy on development of acute diabetes complications in children. Were examined 2 groups of children with diabetes mellitus (DM), which were treated by continuous subcutaneous insulin infusion (CSII) and multiple daily insulin injections (MDII), in which we studied the frequency of acute complications, daily dose of insulin, glycemic control. The frequency of severe acute complications in group CSII considerably decreased with a significant reduction for severe hypoglycemia already on the second year of treatment and for diabetic ketoacidosis (DKA) – on the first. In a MDII group significant dynamics of frequency of acute complications did not occur. In children who received CSII, the level of HbA1c tended to decrease and significantly decreased about 12 month of treatment. Children who were treated by MDII, HbA1c levels did not change significantly despite the increase of the frequency of use of these children insulin analogues short and long action and significant increasing insulin daily dose on the 2nd and 3rd years of treatment.